Development of a low-cost solar-powered water supply system for small-scale drip irrigation farms in Sub-Saharan Africa: Dosing tank and bell siphon perspective - Danso, E.F.; Atta-Darkwa, T.; Plauborg, F.; Sabi, E.B.; Kugblenu-Darrah, Y.; Abenney-Mickson, S.; Andersen, M.N. (My University, 2018)
A substantial amount of work has been done concerning the use of siphons to automatically start and stop the discharge of fluid in many applications, except for application as a water supply system for smallholder drip irrigation systems. Thus, the main aim of this study was to develop a siphon apparatus and apply it to regulate the low-flow-rate water supply from a solar-powered pump as intermittent doses to pressurize small-scale drip irrigation farms in Sub-Saharan Africa (SSA). A siphon apparatus was assembled from polyvinyl chloride (PVC) pipes and installed in a 210-L tank. A drip irrigation system covering an area of 500 m2 was connected to the tank containing the siphon, and water was lifted into the tank by a low-capacity 12-V pump that was powered by a 50-W solar panel. The siphon apparatus in the tank was tested over extended periods of time and was shown to work reliably and consistently by automatically and intermittently discharging water to pressurize the drip irrigation laterals, thus being able to irrigate while largely unattended. Test results showed that the inflow rate of 4.75 L min-1 successfully caused the siphon to start, and the average coefficient of discharge for the siphon was found to be 0.35. Results from water application uniformity tests calculated using the method established by the American Society of Agricultural and Biological Engineers (ASABE) showed average to good discharge uniformity from emitters. The setup cost of the system was USD 415, whereas the net farm income obtained by accounting for all variable costs and annualized capital cost of the irrigation setup was USD 69.We conclude that it should be fairly easy and economically feasible to adapt the dosing siphon, low-flow-rate pump, and solar panel to other small-scale drip irrigation systems that are currently being promoted in SSA. © 2018 American Society of Civil Engineers.
Keywords: Automated irrigation; Low-capacity pump; Poverty alleviation; Smallholder farmers; Water application uniformity